Balinese People’s Happiness in Socio-Economic and Cultural Perspectives - Prastyadewi, Made Ika; Gde Bayu Surya Parwita; Gede Antok Setiawan Jodi (Mudra Jurnal Seni Budaya, 2024)
Happiness becomes a benchmark of how people assess their lives, not only in terms of economic but also social and cultural. This research analyzes how Balinese people perceive happiness in terms of social, economic, and artistic. Quantitative and qualitative approaches were combined in the study. Denpasar City was chosen as the research location considering that Denpasar City is the capital of Bali Province, which acts as the centre of government and economy but still has traditional cultural values that its people closely carry. Data collection using questionnaires was distributed to 100 respondents. Data was analyzed descriptively, and correlation analysis was used to see how much economic, social, and cultural influences on people's happiness in Denpasar City. Information from in-depth interviews was analyzed using word clouds to see how people perceive happiness. The results show that happiness is viewed in terms of economy, income, life, culture, and satisfaction. Both economic, cultural, and social are still variables that influence happiness. The interview results also show that compared to those with high incomes, people feel happier when they gather with family and the surrounding community while doing various religious activities closely related to Balinese culture.